The Tensions of Strategic Communication Decision-Making: An Exploratory Examination of Theory and Practice (Journal of International Crisis and Risk Communication Research, 2020)
The Tensions of Strategic Communication Decision-Making (TSCD) is introduced as an applied theory describing the way decision-makers experience a risk or crisis and prioritize their strategic communication responses to maintain positive relationships with their publics. Relational Dialectics Theory is applied to illustrate how tensions between organizations and publics influence communication decisions. The strategic messages used by the World Health Organization regarding the Zika virus mega-crisis provide a backdrop illustrating how TSCD is enacted. Theoretical and practical implications for decision-making suggest that TSCD contributes to a more robust understanding of how the changing context in a crisis prompts the prioritization of strategic messages.